2019
DOI: 10.1007/s12040-019-1085-x
|View full text |Cite
|
Sign up to set email alerts
|

Monazite and xenotime U–Th–Pb $$_{\mathrm{total}}$$ total ages from basement rocks of the (central) Shillong–Meghalaya Gneissic Complex, Northeast India

Abstract: Monazite and xenotime are the two most useful and commonly used geochronometers for deciphering ages from metamorphic rocks. The low analytical cost involved in electron probe micro-analyser chemical dating, ease of sample preparation and abundance in metamorphic rocks of wide P-T conditions make monazite and xenotime dating most widely used technique for age determination amongst metamorphic petrologists. This contribution presents age comparisons between coexisting monazite and xenotime in the basement metap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The SMGC is an isolated part of the Indian Peninsula (Evans, 1964), the northern extension of the Eastern Ghats Mobile Belt (Crawford, 1974) and the NE extension of the CGC (Desikachar, 1974). Recent studies in the SMGC (Bidyananda & Deomurari, 2007;Chatterjee et al 2007Chatterjee et al , 2011Yin et al 2010;Chatterjee, 2017;Borah et al 2019) and CGC (Chatterjee et al 2008(Chatterjee et al , 2010Maji et al 2008;Sanyal & Sengupta, 2012;Mukherjee et al 2017Mukherjee et al , 2018Kumar & Dwivedi, 2019) have observed the same geochronological age from the basement of the SMGC and the CGC and established a significant relationship between the Mesoproterozoic metamorphic terrain and the CGC. Similar coeval metamorphism has been reported in the Proterozoic gneissic complexes of central India during 1.61-1.57 Ga where supra-crustal granulites were metamorphosed under ultra-hightemperature conditions along the southern margin of the CITZ (Bhowmik et al 2005(Bhowmik et al , 2014.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The SMGC is an isolated part of the Indian Peninsula (Evans, 1964), the northern extension of the Eastern Ghats Mobile Belt (Crawford, 1974) and the NE extension of the CGC (Desikachar, 1974). Recent studies in the SMGC (Bidyananda & Deomurari, 2007;Chatterjee et al 2007Chatterjee et al , 2011Yin et al 2010;Chatterjee, 2017;Borah et al 2019) and CGC (Chatterjee et al 2008(Chatterjee et al , 2010Maji et al 2008;Sanyal & Sengupta, 2012;Mukherjee et al 2017Mukherjee et al , 2018Kumar & Dwivedi, 2019) have observed the same geochronological age from the basement of the SMGC and the CGC and established a significant relationship between the Mesoproterozoic metamorphic terrain and the CGC. Similar coeval metamorphism has been reported in the Proterozoic gneissic complexes of central India during 1.61-1.57 Ga where supra-crustal granulites were metamorphosed under ultra-hightemperature conditions along the southern margin of the CITZ (Bhowmik et al 2005(Bhowmik et al , 2014.…”
Section: Discussionmentioning
confidence: 91%
“…The high-grade rocks of the Eastern Ghats Mobile Belt of the Indian Plate correlated with the Napier and Rayner Province in East Antarctica during the Grenvillian orogeny (∼1.0 Ga) (Mezger & Cosca, 1999;Boger et al 2000;Fitzsimons, 2000). The Rodinia supercontinent achieved the highest strength of accretion during the Grenvillian orogeny (∼1.0 Ga), after which drifting was again started from ∼0.75 Ga, finally forming the Gondwana supercontinent during Neoproterozoic times (∼0.5 Ga) (Rogers & Santosh, 2002;Chatterjee et al 2007Chatterjee et al , 2011Li et al 2008;Yin et al 2010;Kumar et al 2017;Borah et al 2019). This orogeny experienced significant magmatism and contraction during the amalgamation of Eastern Gondwana (0.55-0.50 Ga) (Ghosh et al 2004;Collins et al 2007;Biswal et al 2007).…”
Section: Geological Settingmentioning
confidence: 98%
See 1 more Smart Citation
“…The Shillong-Meghalaya Gneissic Complex (SMGC) comprises rocks occurring in the Shillong Plateau, the Mikir Hills (Karbi Anglong, Assam), and as inselberg in the Quaternary sediments of the western Brahmaputra basins (Evans 1964;Crawford 1974;Desikachar 1974) (Figure 1B). The SMGC Precambrian crystalline rocks comprise NNE-striking, steep-dipping, and multiple-deformed amphibolite-granulite facies Paleo/Neoproterozoic ortho-and paragneisses, derived partly from Neoarchean/ Paleoproterozoic protoliths (Nandy 2001;Bidyananda and Deomurari 2007;Yin et al 2010;Majumdar and Dutta 2016;Kumar et al 2017a;Borah et al 2019;Doley et al 2022), deformed diorite plutons of unknown age, and equigranular to blastoporphyritic Early Mesoproterozoic and Late Neoproterozoic to Cambrian granitoid plutons. In the western part of the SMGC (Garo-Goalpara domain) (Figure 1B), the dominant gneisses are para-gneisses comprising biotite gneiss with sillimanite, ±cordierite, ±garnet, Sillimanite-Garnet-Cordierite-Biotite gneiss, calc-silicate gneiss, mafic granulite, para-amphibolite, granodiorite gneiss, granite gneiss, and diorite intrusives (Chatterjee et al 2007;2011).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…On the basis of xenotime dating of high grade (6.5 kbar and 750°C) metapelitic rocks from the parts of Meghalaya, Borah et al (2019) have reported tectonothermal events at 1150, 930, 820 and 500 Ma whereas monazite records only the 500 Ma event. The authors suggested that among the two accessory minerals, xenotime chemical dating is more suitable for the application in complexly evolved metamorphic terranes.…”
mentioning
confidence: 99%